If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = 2x + 2(2x + -3) Reorder the terms: 3(5 + x) = 2x + 2(2x + -3) (5 * 3 + x * 3) = 2x + 2(2x + -3) (15 + 3x) = 2x + 2(2x + -3) Reorder the terms: 15 + 3x = 2x + 2(-3 + 2x) 15 + 3x = 2x + (-3 * 2 + 2x * 2) 15 + 3x = 2x + (-6 + 4x) Reorder the terms: 15 + 3x = -6 + 2x + 4x Combine like terms: 2x + 4x = 6x 15 + 3x = -6 + 6x Solving 15 + 3x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + 3x + -6x = -6 + 6x + -6x Combine like terms: 3x + -6x = -3x 15 + -3x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + -3x = -6 + 0 15 + -3x = -6 Add '-15' to each side of the equation. 15 + -15 + -3x = -6 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = -6 + -15 -3x = -6 + -15 Combine like terms: -6 + -15 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| w-6=-30 | | 5x^2+7=10 | | 14m-12-12m=16 | | 7(1g-4)=3 | | .75x=1017 | | 1/5(15-4p)-1/10(10p+5) | | 5x^2-50x+125=500 | | Y=3/2x+1/2 | | 30p+9q= | | -2-(-61)= | | w-(-16)=-16 | | -49=-7x+21 | | 9(x+7)+4=-9(x-2)-6 | | 12+x/9=-24 | | X/8+10=26 | | r(n)=24-5n | | 18-6x=30 | | U^2-10u+16=0 | | x^3-14x^2=-49x | | -5x+20=85 | | y=-(-1)+4(-1)+5 | | (x-2)+(x-2)+(x-2)=294 | | -45=-5x-80 | | 2x+10y=3 | | c/9-8=167 | | 100+(-3)= | | 6(3+x)=6+8x | | -24=-4x-36 | | 6x+35=125 | | -21=-30-3x | | -2*2+1= | | 1/4(-1)-1 |